1983
DOI: 10.1159/000156108
|View full text |Cite
|
Sign up to set email alerts
|

Learning Set Formation in Slow Lorises (Nycticebus coucang)

Abstract: In primates, learning set formation has been reported in various simian species, but in only few prosimian species. The formation of visual discrimination learning set was tested on a nocturnal prosimian species, slow lorises (Nycticebus coucang). Their performance was higher than that of some New World monkeys. This confirmed the suggestion from the data on black lemurs (Lemur macaco) that there is an overlap between prosimians and simians in learning set ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The test problems were the same as in the experi ment on slow lorises [Ohta, 1983], They consisted of 197 pairs of two-dimensional patterns and 138 pairs of three-dimensional objects (made of 'junk' objects: toys, paper forms, urethane forms, etc. ).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The test problems were the same as in the experi ment on slow lorises [Ohta, 1983], They consisted of 197 pairs of two-dimensional patterns and 138 pairs of three-dimensional objects (made of 'junk' objects: toys, paper forms, urethane forms, etc. ).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…The procedure of the simultaneous discrimination test with a noncorrection technique was also the same as that for lorises [Ohta, 1983]. Of 335 problems, 2 problems were used for habituation, 32 problems for a preliminary discrimination test, 300 problems for a discrimination test, and the last one for the complete learning test.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The test apparatus was the same Wisconsin Gen eral Test Apparatus (WGTA) as used for the experi ment on slow loriscs [Ohta, 1983). During testing there was no light in the room except for a 100-watt white lamp fixed beneath the ceiling o f the test com partment.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Especial ly, the learning set performance is regarded to provide a reasonable measure of learning ability within the order of primates [Fobes and King, 1982]. One of the authors [Ohta, 1983] reported the learning set formation in nocturnal slow lorises (Nycticebus coucang), and the performance of them is higher than that of some New World monkeys. This con firmed the overlap between prosimians and simians suggested by the data on black le murs [Cooper, 1974], and also proposed the necessity of the interspecific comparison un der common experimental conditions.…”
Section: Introductionmentioning
confidence: 99%